Folk Belief on Pancur Gading Site in Deli Tua Village, Sumatera Utara Province, Indonesia - Ayu Febryani; Puspitawati Puspitawati; Trisni Andayani; Wira Fimansyah; Dedi Andriansyah (Research Synergy Foundation, 2021)
Folk belief through magical practices is an integral part of the discussion about the Pancur Gading Site, located in Deli Tua Village, North Sumatra, Indonesia. Through this folk belief, people come with their own goals and purposes. The remains of this site can be seen by the rushing water of the two showers, namely ‘pancuran putri’ (princess shower) and ‘pancuran panglima’ (the commander's shower). People believe by using this water, all the problems in their life can be resolved immediately. Various magical practices are also held to fulfill human desires for the problems they face. The religious behavior of the people who believe in the properties of Pancur Gading is based on the folk belief in the worshiped figures. The legend of Putri Hijau provides a conception of revered supernatural figures, including the princess known as Putri Hijau or Nini Biring, her first brother (kakek naga), the second (kakek meriam), her commanders, and the ancestors who were worshiped according to cultural background of their respective communities. This belief is strengthened by the existence of media from supernatural experts who connect to patients. This paper is an effort to make an inventory of the various folk beliefs and traditions related to the Pancur Gading Site as an intangible cultural heritage.